EFL Students’ Ability to Translate Conversational Implicatures from the American Sitcom Modern Family into Standard Indonesian - Angellia Puspita Anwar; Risnawati Risnawati; Pebri Prandika Putra (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to identify the most dominant translation strategies and evaluate the success rate of students in maintaining pragmatic meanings when translating implicit conversations from the American sitcom Modern Family into Indonesian, using the framework of Peter Newmark (1988) and Grice HP (1989) this study examines how successful EFL students' ability to understand the implicit meanings contained in conversations. This study uses a quantitative descriptive method. The results showed that students used five translation strategies, namely Literal Translation (35%), Word-for-Word Translation (10%), Faithful Translation (7%) and Idiomatic Translation (6%). The Literal Translation strategy is the most dominant strategy used by EFL students, indicating a tendency to prioritize linguistic forms over pragmatic meanings. Meanwhile, the overall success rate in understanding the meaning of pragmatism was at the level of